Evaluation of several flocculants for flocculating microalgae. (December 2015) - Wu, Jinheng; Liu, Jiexia; Lin, Lifang; Zhang, Chengwu; Li, Aifen; Zhu, Yi; Zhang, Yuanming
Highlights: Flocculating microalgae with five flocculants were evaluated. Effects of flocculants on lipid, carbohydrate and protein were evaluated. Microalgae cells were intact during the flocculation process. The cost of using HNO3 as flocculant was found to be the lowest. Flocculated medium could be recycled for cultivation. Abstract: Flocculation of microalgae with chitosan, polyacrylamide, Al2 (SO4 )3, NaOH and HNO3 was evaluated. Their flocculation efficiencies and optimal dosages were discussed. The effects of the flocculants on cells viability were also investigated and the cells were found to be intact during the flocculation process. Moreover, the effects of flocculants on the extractions were evaluated. Lipid content after flocculants treatments showed no significant differences. Carbohydrate content was lower but protein content was higher after NaOH treatment than those after other treatments. Furthermore, the five flocculated media maintained approximate growth yields to that of the fresh medium in microalgal cultivation, indicating the five flocculated media could be recycled, thereby reducing the cost of biodiesel production from microalgae. Finally, economic comparison of the flocculants was made and the cost of using HNO3, including flocculating cells and recycling medium, was found to be the lowest.